Clinicopathological features and reclassification of penile squamous cell carcinoma according to WHO classification 2022 for penile carcinoma with p16 immunohistochemical expression and its prognostic impact - Vaanya Kaushik; Kanthilatha Pai; Anuradha Rao; Swati Sharma (Diagnostic Pathology)
Abstract Introduction Squamous cell carcinoma (SCC) is the most common type of penile cancer, and infection with human papillomavirus (HPV) is one of the most highly associated risk factors. The WHO classification for penile SCC (2022) strongly recommends and advocates penile SCC to be reported as HPV-associated or HPV-independent type in pathology reports. Further, p16 immunohistochemistry (IHC) is recommended to classify SCC into the above major types, although it is not completely reliable for HPV infection. Although there are no established differences in the prognosis or treatment between HPV-associated and HPV-independent penile tumours, there is recent evidence to suggest that HPV-associated SCC may respond better to radiation therapy, immunotherapy, etc. Aim and objectives This study aims to = analyse the clinicopathological features of penile squamous cell carcinoma and reclassify penile SCC into HPV-associated and HPV-independent types to align with the WHO classification of penile carcinoma (2022) and study the expression of p16 by immunohistochemistry. Additionally, we studied the prognostic significance of HPV-associated and independent SCC based on histology and p16 immunostaining. Materials and methods This is a five-year retrospective single-institution study that included all diagnosed cases of penile SCC. Clinicopathological features and p16 expressions were studied and analysed. Results A total of 72 cases of penile SCC were included during the study period. The mean age of occurrence of penile SCC was 58 years. The most common site of the tumor was the glans penis (50.74%). We encountered only 6 cases (8.3%) of HPV-associated type of penile SCC, while the majority belonged to the HPV-independent type (91.7%) based on histology. p16 immunohistochemistry showed positivity in 15 cases (21%) and negativity in 57 cases (79%). Most of the tumors showed favorable features– histological grade I, pathological T1 stage with a low incidence of nodal metastasis. There was a strong association between histological subtyping into HPV-associated and independent SCC with p16 IHC expression (p = 0.015). Classification of penile SCC by histology and p16 expression into HPV associated and independent type showed no prognostic significance with pathological stage but was significant with histological grade and lymph node metastasis.